Short Dental Implants in the Maxillar Sinus Floor Transcrestal Elevation - Valentin Topalo; Fahim Atamni (Romanian Society of Oral Rehabilitation, 2011)
48 patients have been installed 67 short implants through the modified transcrestal osteotome sinus floor elevation (OSFE) (the study group). In 25 cases, to support the single prosthesis, 33 short implants were concomitantly installed along with 42 longer implants (the reference group). Assessment of osteointegration was carried out through analysis of the clinical picture, orthopantomogram and secondary stability of implants. Statistical study included calculation of the mean value, deviation and standard error, indices of Student‟s paired t-test. The height of the newly formed intrasinus bone varied between 1,6 and 4,1mm (3,1±1.2). The mean of the values of the periotest in the reference group was -3,84±0,24, but in the study group it was -3,67±0,24, the statistical difference being insignificant (p>0,05).One year after its insertion, bone resorption at alveolar process in SI (short implants) in the anterior side was 0,15±0,08 mm, in the posterior one it was 0,20±0,10 mm and did not differ (p>0,05) from that around the longer implants. Short implants as well as the long implants, installed through flapless OSFE and without grafting, osteointegrate, contributing successfully to the prosthetic recovery of the patients with severe atrophies in the posterior segments of the maxilla.